Service quality and consumer satisfaction in a local agrifood café: a case study of Jazz Café, Malang Regency - Mushollaeni, Wahyu; Sudirman, Sudirman; Tantalu, Lorine; Suhindra, Rahmad (Journal of Agricultural Socio-Economics (JASE), 2025)
Consumer satisfaction is an emotional response that arises when expectations toward a product or service are fulfilled; conversely, disappointment emerges when those expectations are not met. Amid the rapid growth of the café or coffee shop industry in Malang City, consumer satisfaction has become an increasingly important aspect to consider. However, many business operators have not yet systematically conducted surveys or evaluations of customer satisfaction regarding the services they provide. As a result, the potential for improving service quality remains underutilized. This study was conducted at Jazz Café, located in Jetak Ngasri, Mulyoagung, Dau District, Malang Regency, East Java. The objective of this research is to measure the level of customer satisfaction and to identify service elements that require improvement to enhance service quality. The study employs the Importance Performance Analysis (IPA) method. Data collection was carried out through the distribution of questionnaires containing 19 attributes to 50 respondents. The data processing stages included an analysis of respondent characteristics and IPA analysis, encompassing the measurement of conformity between performance and customer satisfaction, as well as the mapping of service attributes within a Cartesian diagram. The findings indicate that the overall customer satisfaction level is 89.30%, suggesting that the services have met customer expectations. The attribute with the highest satisfaction level is the ease of the payment process, 102.34%, while the lowest is the availability of supporting facilities, 54.78%. The quadrant analysis reveals that most attributes fall into Quadrants II, III, and IV, indicating that customers are generally satisfied with these attributes. However, there are five attributes located in Quadrant I that require greater attention: employee politeness in treating customers, the availability of supporting facilities, comfort and quantity of seating, product and service quality in relation to price, and the café’s interior design. These attributes are considered important by customers, yet their execution remains suboptimal.